2010
DOI: 10.17221/178/2009-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of ultrasonic-assisted protein extraction from brewer's spent grain

Abstract: Tang D.-S., Tian Y.-J., He Y.-Z., Li L., Hu S.-Q., Li B. (2010): Optimisation of ultrasonic-assisted protein extraction from brewer's spent grain. Czech J. Food Sci., 28: 9-17, Response surface methodology was employed to optimise the ultrasonic-assisted extraction of protein from brewer's spent grain. Three variables, namely the extraction time (min), ultrasonic power (W/100 ml of extractant), and solid-liquid ratio (g/100 ml) were investigated. Optimal conditions were determined and tri-dimensional response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 29 publications
(26 reference statements)
2
27
0
Order By: Relevance
“…The concentration of soluble protein in UAE water extracts was 82 ± 1 mg protein/g BSG,dry . This value is of the same order as the one reported by Tang et al [23] in the study of UAE of protein fraction from BSG, with an optimum yield value of 104.2 mg protein/g BSG.…”
Section: Determination Of Extract Componentssupporting
confidence: 84%
“…The concentration of soluble protein in UAE water extracts was 82 ± 1 mg protein/g BSG,dry . This value is of the same order as the one reported by Tang et al [23] in the study of UAE of protein fraction from BSG, with an optimum yield value of 104.2 mg protein/g BSG.…”
Section: Determination Of Extract Componentssupporting
confidence: 84%
“…1b). In addition, Tang et al (2010) found that a higher yield of Brewer's spent grain protein was obtained from a lower solid-liquid ratio than in a higher ratio, which may be caused by the relatively higher protein content in the solution with a higher amount of the liquid than that in a higher ratio when the extraction time reached equilibrium. This phenomenon may be explained by the mass transfer principle and the distribution of ultrasonic energy in the solution, as well as by the lower ratio that has higher concentration gradient, which leads to a higher diffusion rate and extraction yield (Liu et al 2013).…”
Section: Model Fitting and Effects Of Independent Variable On Responsementioning
confidence: 98%
“…This phenomenon may be explained by the mass transfer principle and the distribution of ultrasonic energy in the solution, as well as by the lower ratio that has higher concentration gradient, which leads to a higher diffusion rate and extraction yield (Liu et al 2013). In addition, Tang et al (2010) found that a higher yield of Brewer's spent grain protein was obtained from a lower solid-liquid ratio than in a higher ratio, which may be caused by the relatively higher protein content in the solution with a higher amount of the liquid than that in a higher ratio when the extraction time reached equilibrium.…”
Section: Model Fitting and Effects Of Independent Variable On Responsementioning
confidence: 98%
“…Sugars, for example are efficiently extracted from BSG at temperatures higher than 100°C, especially 120°C when using dilute acid [17] or between 150°C and 190°C when pure water is used as extraction solvent [30]. Proteins can be extracted from BSG by ultrasonic-assisted extraction [31] or ultrafiltratioin [32].…”
Section: Chemical Composition Of Bsg Extractsmentioning
confidence: 99%